2020
DOI: 10.1101/2020.10.27.20220566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and outcomes of co-infection and super-infection with SARS-CoV-2 and other pathogens: A Systematic Review and Meta-analysis

Abstract: Introduction: The recovery of other respiratory viruses in patients with SARS-CoV-2 infection has been reported, either at the time of a SARS-CoV-2 infection diagnosis (co-infection) or subsequently (superinfection). However, data on the prevalence, microbiology and outcomes of co-infection and super infection are limited. The purpose of this study was to examine occurrence of respiratory co-infections and superinfections and their outcomes among patients with SARS-CoV-2 infection. Patients and Methods: We s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 71 publications
2
27
0
3
Order By: Relevance
“…They defined co-infection as the recovery of other respiratory pathogens in patients with SARS-CoV-2 infection at the time of a SARS-CoV-2 infection diagnosis and superinfection as the subsequent recovery of other respiratory pathogens during care for patients infected with SARS-CoV-2. Doing this, they found that as many as 12% of patients with COVID-19 had co-infections and as many as 14% superinfections, the latter being associated with poor outcomes [141]. Bacterial co-infections occurred in 4% (95% CI: 1-8%), and superinfections in 6% (95% CI: 2-11%), viral coinfections occurred in 4% (95% CI: 2-7%) and superinfections in 2% (95% CI: 0-7%), and fungal co-infections in 4% (95% CI: 1-8%), and fungal superinfections in 4% (95% CI 0-11%).…”
Section: How To Treat Cap In the Covid-19 Eramentioning
confidence: 98%
See 1 more Smart Citation
“…They defined co-infection as the recovery of other respiratory pathogens in patients with SARS-CoV-2 infection at the time of a SARS-CoV-2 infection diagnosis and superinfection as the subsequent recovery of other respiratory pathogens during care for patients infected with SARS-CoV-2. Doing this, they found that as many as 12% of patients with COVID-19 had co-infections and as many as 14% superinfections, the latter being associated with poor outcomes [141]. Bacterial co-infections occurred in 4% (95% CI: 1-8%), and superinfections in 6% (95% CI: 2-11%), viral coinfections occurred in 4% (95% CI: 2-7%) and superinfections in 2% (95% CI: 0-7%), and fungal co-infections in 4% (95% CI: 1-8%), and fungal superinfections in 4% (95% CI 0-11%).…”
Section: How To Treat Cap In the Covid-19 Eramentioning
confidence: 98%
“…However, in the literature reviewed there is often not a clear delineation made by the authors between co-infections and secondary/superinfections. In the most recent preprint of a systematic review and meta-analysis, the authors attempted to dissect out co-infections from superinfections [141]. They defined co-infection as the recovery of other respiratory pathogens in patients with SARS-CoV-2 infection at the time of a SARS-CoV-2 infection diagnosis and superinfection as the subsequent recovery of other respiratory pathogens during care for patients infected with SARS-CoV-2.…”
Section: How To Treat Cap In the Covid-19 Eramentioning
confidence: 99%
“…This scale consists of 27 items that assess study characteristics, such as internal validity (bias and confounding), statistical power, and external validity. We scored studies as low risk (score 20-27, medium risk (score [15][16][17][18][19], or high risk (score ïżœ14).…”
Section: Plos Onementioning
confidence: 99%
“…Co-infections, diagnosed around the time of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, appear to be uncommon occurring in 0.6% to 3.2% of patients [2][3][4][5]. Bacterial respiratory coinfections with Streptococcus pneumoniae or Staphylococcus aureus are the most common causes of coinfections, whereas respiratory viral co-infections appear to be relatively rare [4,6].…”
Section: Introductionmentioning
confidence: 99%